GaAs manufacturing processes conditions for micro- and nanoscale devices. (December 2020) - Joint, F.; Abadie, C.; Vigneron, P.B.; Boulley, L.; Bayle, F.; Isac, N.; Cavanna, A.; Cambril, E.; Herth, E.
Abstract: High aspect-ratio etchings are a key aspect of the fabrication of III–V semiconductor devices. The increasing demand for diverse geometries with various characteristic lengths (from the micro- to the nano-meter scale) requires the constant development of new etching recipes. In this article, we demonstrate a versatile mask-plasma combination for micro- and nanofabrication of GaAs substrate using an Inductive Coupled Plasma-Reactive Ion Etching (ICP-RIE) system. We identify five recipes at 25  ° C, with high selectivity, and apply them on one photoresist (AZ4562) and two hard (chromium and nickel) masks. The optimized etching plasma chemistry (BCl 3 /Cl 2 /Ar/N 2 ) shows a pattern transfer on GaAs with a high rate ( ≥ 5.5  μ m/min), a high anisotropy, a high selectivity ( > 4:1 with photoresist mask, and > 50:1 with hard masks), a good etch surface morphology, and smooth sidewalls profile ( > 88 ° ). Herein, we detail the requirements definition, the engineering processes with detailed recipes, the verification, and validation of three device geometries (ridges, cylinders, and nanopillars). The presented results can be valuable for a wide range of applications from the microscale to the nanoscale, and are compatible with a manufacturing process using only a single commercial ICP-RIE tool with two chambers dedicated, respectively, for metallic masks and photoresist mask.